Analisis Livelihood Strategy Masyarakat Suku Baduy pada Masa Pandemi Covid-19 - Prabowo, Andi; Syakirah, Bella; Azura A.A., Diva; Putri, Nadia (Saskara : Indonesian Journal of Society Studies, 2023)
Livelihood Strategy is an activity or effort to be able to meet the needs of life. Thispaper is intended to explain the strategy for meeting the needs of life (Livelihood Strategy)for the people of Gajeboh Village. Gajeboh Village is one of the villages located in KanekesVillage, Leuwidamar District, Kab. Lebak, Banten. This study aims to determine theimplementation of the Livelihood Strategy in Gajeboh Village which consists of the livingconditions of the people of Gajeboh Village during the Covid-19 pandemic, theimplementation of the Livelihood Strategy of the people of Gajeboh Village, and themechanism of the Livelihood Strategy of the people of Gajeboh Village. This research wasconducted on 5-7 November 2021 on a Field Trip activity in Gajeboh Village, KanekesVillage, Leuwidamar District, Lebak Regency, Banten. In this study, the researcher used aqualitative descriptive research method. Collecting data using interactive techniquesconsisting of in-depth interviews, role-playing observations, and documentation with fourresource persons regarding the implementation of the Livelihood Strategy in GajebohVillage, Kanekes Village, Leuwidamar District, Kab. Lebak, Banten. The data were analyzedusing three activity lines in interactive data analysis, namely data reduction (data editor),data display (data presentation), conclusion drawing/verification. The Covid-19 pandemichas had a negative impact on the economy of the people of Gajeboh Village Baduy in theprocess of market mechanisms and decreasing tourist visits. However, in daily life, especiallyin terms of meeting needs, it does not have a significant impact. The people of GajebohVillage Baduy implement a livelihood strategy by utilizing five capitals consisting of humancapital, natural capital, financial capital, social capital, and physical capital. Theconstruction of the application of the five social capitals is a contributor to the ongoingmechanism of the livelihood strategy, namely intensification, extensification, diversification,and spatial engineering. The four models serve as indicators for the implementation of the“Farm” strategy, which consists of the “On-Farm” strategy of combining intensification andextensification, and the “Non-Farm” strategy of combining diversification and spatialengineering.